THE DEVELOPMENT OF NUCIFERA CREATIVE COTTAGE AS AN INTEGRATED COCONUT PROCESSING CENTER IN MUNTE VILLAGE, WEST LIKUPANG DISTRICT, NORTH MINAHASA REGENCY, NORTH SULAWESI - Retno Lestari; Yasman Yasman; Ewin Nurdin; Windya Fajira; Arkan Askarillah Hidayat; Salsabila Isha; Hedza Fadli Robbina (Center for Rural Areas Empowerment (P2D), Institut Teknologi Bandung, 2024)
Munte Village in Likupang Barat District, North Minahasa, North Sulawesi lacks both food and non-food industries, despite the district's abundance of commodities, one of which is coconut with a total land area of 2,595.18 hectares. This indicates that the potential in Likupang Barat District, especially in Munte Village, is not matched with the use of innovative processing technology, resulting in its underutilization. Through this program, the community is empowered to utilize coconuts for the production of virgin coconut oil (VCO) and liquid organic fertilizer as Munte Village's flagship products. These products are expected to provide innovation and inspiration for the advancement of the biodiversity-based economy sector in Munte Village, thereby maximizing the available benefits to support the local economy. Additionally, it is aimed that these products will become distinctive souvenirs Munte Village, contributing to the development of the tourism sector in that area. As a result, residents of Munte Village who participated in the socialization and workshops have successfully produced these flagship products by harnessing coconut as a local biodiversity resource.